Соціальна робота з дослідження стану адаптпції дітей внутрішньо переміщених осіб до нового соціального середовища - Корпач, Надія; Сидорук, Ірина (My University, 2018)
У статті автори відобразили результати дослідження навчальної та соціально-психологічної адаптації школярів із внутрішньо переміщених сімей до змінного нового мікросередовища. Визначено рівні соціальної адаптації: високий, середній, недостатній та розкрито зміст їх показників. Обґрунтовано, що високий рівень вирізняється достатньою для школярів адаптацією, середній рівень фактично рівень ситуативної адаптації, недостатній рівень – школярі переважно пасивні й у навчальному процесі, і у позакласній роботі. Аналіз результатів проведеного дослідження школярів із внутрішньо переміщених сімей засвідчує, що більшість із них пройшли найскладніші етапи адаптації. Проте, для окремих дітей цієї категорії адаптивні процеси на певному етапі зупиняються і не просуваються у позитивному напрямі. Інша частина перебуває у «групі ризику» і потребує значної уваги з боку шкільних соціальних педагогів, соціальних працівників. In the article, the authors presented the results of the study of educational and socio-psychological adaptation of schoolchildren from internally displaced families to a new micro-environment variable. The levels of social adaptation are defined: high average, insufficient and disclosed content of their indicators. For a high level of adaptation, the stable satisfaction of children is characterized by the situation they occupy in the institution of general secondary education, there is no difficulty in learning, active participation outside the classroom, social life of the class and school. Peculiar self-confidence, sociability, the presence of a wide range of friends. A sense of full privacy in a family environment. The average level is the level of situational adaptation. Satisfaction of children with their position in the classroom, but there is a low status in interpersonal relationships. Anxiety sensation in the new learning expectations of knowledge control and control. Responsibility for their actions and actions is situational. Manifestations of passivity, may change with the desires of active activity. Insufficient level - passivity of students in the educational process and in extracurricular work. An analysis of the results of a study conducted by schoolchildren from internally displaced families shows that most of them have passed the most difficult stages of adaptation. However, for some children of this category, adaptive processes at a certain stage stop and do not move in a positive direction. The other part is in the "risk group" and needs a lot of attention from the school social educators.
Keywords: соціальна адаптація; навчальна адаптація; соціально-психологічна адаптація; школярі; внутрішньо переміщені сім’ї; рівні адаптації; social adaptation; educational adaptation; social-psychological adaptation; schoolchildren; internally displaced families; levels of adaptation